Perancangan Website Sissenrekang Sebagai Media Promosi dan Sistem Informasi Wisata Alam Kabupaten Enrekang - Amelia, Rina; Jamil, Muhammad; Aris, Valentino (Jurnal Riset Rumpun Ilmu Ekonomi, 2026)
This study aims to develop the sissenrekang.com website as a promotional medium for tourism in Enrekang Regency. The development was carried out using the WordPress CMS with the Research and Development (R&D) research method and the Four-D model (Define, Design, Develop, Disseminate), starting from the needs analysis stage, design, sketching, to creating a digital mockup. The functional validation results obtained a score of 100%, indicating full system feasibility. Further evaluation through Functional Suitability Analysis, Guttman Scale, and System Usability Scale (SUS) resulted in a score of 81.375, indicating a high level of feasibility and comfort of use. This website is expected to provide benefits for managers, facilitate access to information for users, and contribute to supporting the promotion and development of tourism in Enrekang Regency.